Membentuk Karakter Peserta Didik yang Berilmu dan Bertaqwa - Melsya Dwi Putri; Fadila Aulia Putri; Putri Diana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims examine the concepts of knowledge and piety in the Al-Qur'an and their implementation in education, with a focus on Surah Ali Imran verse 18. The method used is literature study. The research results show that knowledge and piety have a close relationship and complement each other in forming a person with integrity. The integration of science and pious values ​​in the educational curriculum can be done through subject matter that reflects the concepts of monotheism, justice and respect for knowledge. Programs and activities that support the development of students' character and spirituality include taushiah, 3S empowerment (Smile, Greet, Greetings), reading short letters, and prayer before studying. Implementation of the values ​​of Surah Ali Imran verse 18 in daily life includes practicing monotheism, pursuing knowledge throughout life, upholding justice, and being a good example. This research concludes that the integration of knowledge and piety in education is very important forming a generation that is intellectually intelligent and has strong character and spirituality.